Innovation as an Element of Strategic Management Accounting - T. S. Hudaib (Учёт. Анализ. Аудит, 2018)
Strategic management accounts (SMA) is designed to maintain the optimal position of the economic entity in the external environment. Such position is supported through implementation of a set of measures based on the elements and characteristics of SMA which makes it possible to use fully the whole potential of the production system. This system is based on the principles of production efficiency and allows the fluctuations in socio-economic indicators measuring the performance of an economic entity in a certain period of time and in a certain economic zone. A possible way to achieve this effect is to create the company’s reproductive circuit, which has an innovative basis. The reproduction circuit is a set of conditions aimed at the continuous implementation of reproductive processes in relation to the resource potential of an economic entity, which allows and stimulates the introduction in its production process a number of innovation technologies to get additional effect in accordance with the requirements of intensification.The reproduction circuit is divided into external and internal. The former forms a set of external stimulation actions, and the latter is focused on the use of inducing action of information and technological nature, as well as an internal mechanism of the enterprise.Consolidation of the external and internal reproduction circuit determines the efficiency of each production unit of the economic entity, taking into account the speed of its adaptation to the new operating conditions by different parameters.Elements and characteristics of SMA are those functions that make SMA uniquely different from other forms of accounting (management accounting and financial accounting). This article represents the relevance of the analysis of innovations, as one of the elements of SMA.